Z1
a)(x-2-3)-(z+5)+(x+4)
b)(3a-2)-(a+4)+(a-3)
c)4(2y-7ykwadrat)-3(ykwadrat-3y)
d)-5(2b+3z)+2(2b-4z)
z2Wyłacz wspólny czynnik przed nawias
a) 4x-8y-4z
b)6a-9b+12y
c) 12akwadrat+8m-20
d)5akwadrat-15b+20c
e)30x+18y-6
f)36a+12b-6
g)63m+54n-9
h)3,5a+0,7b-14

2

Odpowiedzi

2010-01-24T19:37:20+01:00
Z1
a) (x-2-3)-(z+5)+(x+4)= x-5-z-5-x-4= -14-z
b) (3a-2)-(a+4)+(a-3)= 3a-2-a-4+a-3= 3a-9
c) 4(2y-7ykwadrat)-3(ykwadrat-3y)= 8y-28ykwadrat-3ykwadrat-9y=-y-25ykwadrat
d) -5(2b+3z)+2(2b-4z)=-10b-15z+4b-8z= -6b-23z



;***************************



z2
c) 12akwadrat+8m-20= 4(3akwadrat+2m-5)
d) 5akwadrat-15b+20c= 5(akwadrat-3b+ac)


myśle, że pomogłam
  • Użytkownik Zadane
2010-01-24T19:39:01+01:00

z2Wyłacz wspólny czynnik przed nawias
a) 4x-8y-4z=4(x-2y-z)
b)6a-9b+12y=3(2a-3b+4y)
e)30x+18y-6=6(5x+3y-1)
f)36a+12b-6=6(6a+2b-1)
g)63m+54n-9=9(7m+6n-1)
Tyle umiem. Mam nadzieję że jakoś pomogłam :)
1 5 1